Natural Rubber Latex Allergy Update - Faustino, Lilia (Operating Room Nurses Association of Canada Journal, 1999)
Latex allergy is a major health issue, not only to health care workers who provide direct patient care but also to individuals in environmental services, dietary, and pharmacy, engineering and medical record departments who also have potential for sensitization.